Literature Review: Asupan Gula, Garam, dan Lemak dengan Kejadian Obesitas - Safira Andjani (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Obesity can occur in all age groups. Obesity can have an impact on an individual's physical health, as well as social and economic well-being. Energy intake constitutes a critical component in supporting the body's physiological functions and overall health. Energy is obtained from the foods and beverages a person consumes, which contain various food ingredients. However, some of these ingredients such as sugar, salt, and fat can pose health risks when consumed in excess of the recommended daily limits. This literature aims to review and analyze research findings related to the intake of sugar, salt, and fat in relation to obesity. The articles reviewed were published in both Indonesian and English within the last five years (2021–2025), and were sourced from online databases. The majority of the studies reviewed indicate a correlation between sugar, salt, and fat intake and obesity.